Development and Quality Evaluation of Gluten-Free Wafer Sheets Enriched with Strawberry Powder for Use in the Production of Gluten-Free Ice Cream Cones - Hülya GÜL; Sultan ACUN; Ayşe Nur KORKMAZ; Ebru POLAT; Nurhan Sonay SAYGILI; Tuğba TÜRKER (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Food Science and Technology)
This study aimed to develop gluten-free wafer sheets (GFWS) by using strawberry powder (SP) with improved nutritional, technological, and sensory properties for use in gluten-free ice cream cone (GFIC) production. The gluten-free flour mixture (GFFM), comprising corn and rice flour, corn, and potato starch, was enriched with SP at varying ratios (0%, 10%, 20%, and 30%) to accomplish the designated goal. GFWS produced by adding SP was evaluated in terms of physical, chemical, textural, and sensory properties. As the SP substitution level increased, the GFWS's thickness, redness, and ash content increased while its width, brightness, moisture content, and pH decreased. When the amount of SP in the GFFM was increased, the hardness and fracturability of the GFWS showed a reduction. The inclusion of SP in GFWS led to a proportional increase in their nutritional fiber content. Regarding sensory attributes, the GFWS fortified with SP exhibited higher overall acceptability ratings than the control group (without SP). The study's results demonstrated that incorporating 30% SP into the GFFM could produce GFWS and GFIC with improved functional characteristics and satisfactory technological and sensory attributes.